2022
DOI: 10.3390/vetsci9040184
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Clinical Pathological Presentation of 310 Dogs Affected by Lymphoma with Aberrant Antigen Expression Identified via Flow Cytometry

Abstract: Phenotypic aberrancies have been reported occasionally in canine lymphomas. Here, we retrospectively collected 310 canine lymphomas with an aberrant phenotype detected via flow cytometry and describe their clinical and clinical pathological features at diagnosis. There were 152 T-cell lymphomas not otherwise specified (T-NOS), 101 T-zone lymphomas (TZL), 54 B-cell lymphomas, and 3 cases with two suspected concurrent neoplastic populations. The most represented aberrancies were: CD5-, CD4-CD8-, and CD3- in T-NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The protein network for canine TZL, for example, shows a key group of modulated proteins, such as ESR1, GATA4, CD44, CRBP1, ACTA1 (Figure 6), all consistent with the human T-cell NHL cases [79][80][81] .…”
Section: Network Regulation Analysismentioning
confidence: 65%
“…The protein network for canine TZL, for example, shows a key group of modulated proteins, such as ESR1, GATA4, CD44, CRBP1, ACTA1 (Figure 6), all consistent with the human T-cell NHL cases [79][80][81] .…”
Section: Network Regulation Analysismentioning
confidence: 65%
“…The possibility of TZL originating from the tongue is also high in this dog, considering a previous case of TZL in the tongue ( 32 ). However, in another study, 5.3% of T-cell not otherwise specified dogs were identified as CD45- ( 20 ). Although this study did not find any aggressive lymphoma with CD45-, it is expected that the frequency of this aberrant type will increase as the population size increases.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have reported a slight difference in the incidence of aberrant phenotypes depending on the definition used. Specifically, Celant et al found that 12% (310/2,612) of dogs had specific antigen aberrancies ( 20 ), while Wilkerson et al reported an incidence of 22% ( 5 ). The incidence of loss of MHCII expression or low expression, which was the most frequently identified aberrancy in our study, has been reported to be approximately 14–72% in previous studies ( 2 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They appear to be CD45+ T-cells because of the concomitant expression of CD3 ( Figure S2 ) and warrant further consideration. First, the co-expression of these two markers should not always be considered aberrant and thus diagnostic for neoplasia, as was the case in the past [ 20 , 21 ]. Second, the nMFI of both CD5 and CD21 was different from those of the remaining small cells, further supporting the distinct nature of CD5+CD21+ cells.…”
Section: Discussionmentioning
confidence: 99%